A streamlined workflow for a fast and cost-effective count of tyndallized probiotics using flow cytometry - Bolzon, Veronica; Bulfoni, Michela; Pesando, Massimo; Nencioni, Alessandro; Nencioni, Emanuele (Frontiers in Microbiology, 2024)
The use of dead probiotics and their cellular metabolites seems to have immunomodulating and anti-inflammatory properties giving protection against pathogens. These inanimate microorganisms, often referred to as tyndallized or heat-killed bacteria, are a new class of probiotics employed in the clinical practice. Safety concerns regarding the extensive use of live microbial cells has increased interest in inactivated bacteria, as they could eliminate shelflife problems and reduce the risks of microbial translocation and infection. Culture dependent methods are not suitable for the quality assessment of these products, and alternative methods are needed for their quantification. To now, bacterial counting chamber and microscopy are used for tyndallized bacteria enumeration, but no alternative validated methods are now available for the commercial release. Aim of the present work is to design a new method for the qualitative and quantitative determination of tyndallized bacterial cells using a flow cytometric technology. Using a Live/Dead Viability assay based on two nucleic acid stains, Thiazole Orange (TO) and Propidium Iodide (PI), we optimized a workflow to evaluate of bacterial viability beyond the reproduction capacity and that provides information about the structural properties and metabolic activities of probiotics, on Facs Verse, without employing beads as a reference. Data obtain in this study represents the first analytical application that works effectively both on viable and non-viable cells. Results provided consistent evidence with different samples analysed using the same staining protocol, and acquisition settings. No significant discrepancies were highlighted between declared specification of commercial strain and analytical data obtain. For the first time, flow cytometry was employed for counting tyndallized bacterial cells as a quality control assessment in probiotic production. This aspect becomes important if applied to medical devices where we cannot boast metabolic but only mechanical activities.